PERANCANGAN KURSI RODA ERGONOMIS UNTUK ORANG MANULA - Dewi Putri Mardiana; M.Rif’an Pujianto; Sulistyo Sulistyo (Journal of Industrial Engineering and Technology, 2020)
In designing ergonomic products, anthropometric data are needed to determine the size of the product that fits the user's body so that it can make users feel comfortable when using the product. This paper discusses the design of ergonomic wheelchair products for elderly people who need adult anthropometric data to determine the size of wheelchair products that will be used later. From the anthropometric data, the percentile value is calculated which is then determined the size of the wheelchair product.